Filsafat Pendidikan Aliran Psikologi Behavioristik dan Pendidikan Berbasis Kompetensi - Fattah Hanurawan (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2005)
Behaviorism as system of thought has its roots in a number of philosophical traditions: materialism, empirism, and positivism. Behavior-istic psychology applied to the educational context has resulted in several educational policy emphases and specific instructional practices, i.e. behavioral objectives, instructional strategies, and competency based education. The emphases in competency based education are on the outcomes rather than the process of learning. The advocates of behavioral education maintain that learning outcomes should be measured objectively and precisely.